2018
DOI: 10.32598/immunoregulation.1.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resistance Training with Theraband on the Transforming Growth Factor-β in the Elderly Women

Abstract: Background: Ageing and physical inactivity can negatively affect immune system. On the contrary, a healthy lifestyle and physical activity can improve immune system and prevent from mild inflammatory diseases. Transforming Growth Factor-β (TGF-β) can play an important role in the regulation of immune function and inflammation. This study aimed to investigate the effects of 8 weeks of theraband resistance training on the plasma level of TGF-β in the elderly women. Materials and Methods:Eighteen inactive elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…This result is clinically important because high circulating levels of TGF-β1 are associated with worse survival in breast cancer and contribute to the reduction of muscle mass and muscle weakness (50). This finding is consistent with that of Rajabi et al (36) who showed a reduction in plasma TGF-β1 levels in elderly women after an RT protocol. Although other studies have not observed a reduction in TGF-β1 after RT (9,39), the population (e.g., obesity or osteoarthritis patients or men) and intervention strategy (elastic band RT or diet) were different from our study.…”
Section: Discussionsupporting
confidence: 93%
“…This result is clinically important because high circulating levels of TGF-β1 are associated with worse survival in breast cancer and contribute to the reduction of muscle mass and muscle weakness (50). This finding is consistent with that of Rajabi et al (36) who showed a reduction in plasma TGF-β1 levels in elderly women after an RT protocol. Although other studies have not observed a reduction in TGF-β1 after RT (9,39), the population (e.g., obesity or osteoarthritis patients or men) and intervention strategy (elastic band RT or diet) were different from our study.…”
Section: Discussionsupporting
confidence: 93%
“…The load was adjusted by applying the scale every 2 weeks until the perceived level of difficulty gradually reached the eighth level on the scale. An elastic band progressive resistance exercise program was designed according to the guidelines of the American College of Sports Medicine (ACSM) [ 19 ]. Strengthening exercises were started in the first week as 1 set and 10 repetitions.…”
Section: Methodsmentioning
confidence: 99%